Spiritualitas Sang Nabi (Analisis nilai dekonstruksi dalam puisi prosa Sang Nabi karya Kahlil Gibran) - Muhammad Zuhdi; Rista Aulia Sholikhah (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
There is no one ever doubts the quality of Kahlil Gibran as a poet or man of letters. His great name is the guarantee of his literature works' quality. Almost every work, most of them are prose poetry, gain great success, and one of the indications is by translating into various languages in the world, including Indonesian. One of his most success works and receives international acknowledgment as well as his own admission as his best work is The Prophet. The Prophet includes many lessons bearing deconstruction values, which has been proven in this study. Deconstruction values within The Prophet is still inherent in each statement of its main character (Al Mustafa/Gibran) about topic concerning with many kinds of human problems, such as love, marriage, child, friendship, beauty, happiness, sadness, work, religion, and even death. In this study those values were contrasted or compared to various realities in form of text and social fenomena of the community in order to find their contradictions or similarities. This qualitative study used moral approach because its review material is intrinsic aspect of a literature works related to values. While the analysis technique used content analysis because it tried to disclose, understand, and catch the massage beneath the literature work. While the